Quantification and herbicidal activity of mimosine from Leucaena leucocephala (Lam.) de Wit - Nornasuha, Yusoff; Ismail, Sahid; Muhamad Safwan, Ishak; Fatimah Sh, Bajrai; Khairiatul Mardiana, Jansar (2017)
Laboratory experiments have been performed to quantify the amount of mimosine (an allelochemical) from Leucaena leucocephala and evaluate the herbicidal activity of mimosine on selected invasive weeds in Malaysia. The mimosine amount in an aqueous extract of shoot, mature leaf, and seed parts of L. leucocephala were quantified by utilizing high-performance liquid chromatography. The herbicidal activity of mimosine was tested on the growth (i.e., radicle length, shoot length, and fresh weight) of three selected invasive weed species (i.e., Ageratum conyzoides, Emilia sonchifolia, and Tridax procumbens) in five different concentrations (i.e., 0, 10, 25, 50, and 100 ppm) by utilizing the bioassay petri dish method. The mimosine amount was highest in the shoot aqueous extract (1.41 × 104 ppm), followed by the seed aqueous extract (8,463 ppm), and finally, the mature leaf aqueous extract (1,881 ppm). Mimosine inhibited the growth of weed species as the concentration increased. More than 50% inhibition of all the bioassay weed species was observed when they were applied at the mimosine concentrations of 50 and 100 ppm. These results provide benchmark information for controlling weeds in the agriculture field in a sustainable manner and for the future development of bioherbicides.